Pelaksanaan Pendaftaran Hak Atas Tanah Berdasarkan PERMEN ATR/BPN Nomor 6 Tahun 2018 tentang Pendaftaran Tanah Sistematis Lengkap Oleh Kantor Pertanahan Kabupaten Boalemo (International Forum of Researchers and Lecturers, 2023)
The Complete Systematic Land Registration Program (PTSL) carried out by the government based on Minister of Agrarian Regulation number 6 of 2018 is the first land registration activity carried out simultaneously for all land registration objects throughout the territory of the Republic of Indonesia in one village/kelurahan or other name. at the same level, which includes the collection of physical data and juridical data regarding one or several land registration objects for registration purposes with the aim of providing legal certainty and legal protection of land rights in a definite, simple, fast, smooth, safe, fair, equitable and open manner. and accountable so that it can improve the welfare and prosperity of society and the country's economy as well as reduce and prevent land disputes and conflicts. The research method used in this research is sociological juridical legal research and descriptive analysis with a qualitative approach. The results of this research show that the mechanism for implementing the Complete Systematic Land Registration Program (PTSL) by the Boalemo Regency Land Office has been carried out based on the procedures mandated in the Regulations. Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning Complete Systematic Land Registration which includes: Planning Stage, Location Determination, Preparation, Formation and Determination of the PTSL Adjudication Committee and Task Force (SATGAS), Counseling, Collection of Physical Data and Data Juridical, Juridical Data Research for Proving Rights, Announcement of Physical Data and Juridical Data and Validation, Completion of PTSL Activities, Confirmation of Conversion, Recognition of Rights and Granting of Rights, Bookkeeping and/or Issuance of Certificates, Documentation and Submission of Activity Results and Reporting of PTSL Activity Results. Although the mechanism for implementing the Complete Systematic Land Registration Program (PTSL) by the Boalemo Regency Land Office has been carried out in accordance with procedures. Thus, at the implementation level there are still obstacles in implementing the Complete Systematic Land Registration Program (PTSL) which is oriented towards quantity targets which makes it possible to ignore quality. As for the obstacles faced, both internal obstacles are obstacles faced by the Boalemo Regency Land Office that come from within the agency and External Obstacles are obstacles faced that come from outside the Boalemo Regency Land Office agency.